Using APOS Theory Framework: Why Did Students Unable To Construct a Formal Proof? - Syamsuri, Syamsuri; Purwanto, Purwanto; Subanji, Subanji; Irawati, Santi (Universitas Ahmad Dahlan, 2017)
Mathematical thinking is necessary in mathematics learning especially in college level. One of activities in undergraduate mathematics learning is proving. This article describes studentsâ thinking process who unable to construct mathematical formal proof. The description uses APOS Theory to explore studentsâ mental mechanism and studentsâ mental structure while they do proving. This research is qualitative research that conducted on students majored in mathematics education in public university in Banten province, Indonesia. Data was obtained through asking students to solve proving-task using think-aloud and then following by interview based task. Results show that the students could not construct a formal proof because they unable to appear encapsulation process. They merely enable to think interiorization and coordination. Based on the results, some suitable learning activities should designed to support the construction of these mental mechanism.